On the Spectrum of a Discrete Non-Hermitian Quantum System - Ergun, E. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
In this paper, we develop spectral analysis of a discrete non-Hermitian quantum system that is a discrete counterpart of some continuous quantum systems on a complex contour. In particular, simple conditions for discreteness of the spectrum are established.